Comparison of long‐term mortality according to obesity in patients with successful percutaneous chronic total occlusion interventions using drug‐eluting stents. Issue 4 (8th May 2017) - Won, Ki‐Bum; Yoon, Hyuck‐Jun; Lee, Sang‐Gon; Cho, Yun‐Kyeong; Nam, Chang‐Wook; Hur, Seung‐Ho; Lee, Seung‐Whan; Lee, Pil‐Hyung; Ahn, Jung‐Min; Park, Duk‐Woo; Kang, Soo‐Jin; Kim, Young‐Hak; et al.
Abstract : Objective: To evaluate the long‐term mortality according to obesity in patients with chronic total occlusion (CTO) lesions after successful percutaneous coronary intervention (PCI). Background: Despite the potential impact of coronary revascularization and lesion severity on the obesity paradox, the long‐term survival according to obesity in CTO patients after successful PCI has been unknown. Methods and results: Between January 2003 and September 2014, we examined 1, 172 consecutive Korean patients with 1, 190 CTO lesions who underwent successful drug‐eluting stent (DES) implantation in two tertiary academic medical centers. The primary and secondary endpoints were all‐cause and cardiac death, respectively. Obesity was defined as a body mass index ≥25.0 kg/m 2, based on the criteria for Asians. The median follow‐up time was 4.4 years. The prevalence of obesity was 54.4%. During the follow‐up periods, the occurrence of all‐cause (6.1 vs. 10.7%) and cardiac death (3.8 vs. 6.7%) was lower in obese patients than in non‐obese patients ( P <0.05, respectively). Kaplan–Meier analysis showed that obese patients had lower cumulative rates of all‐cause and cardiac death than did non‐obese patients (log‐rank P <0.05, respectively). Univariate Cox regression analysis showed that age ≥65 years (hazard ratio [HR], 3.62), diabetes mellitus (HR, 1.94), renal dysfunction (HR, 7.03), systolic heart failure (HR, 2.61), and obesity (HR, 0.58) were associated with all‐cause death ( P <0.05). Multivariate Cox regression models showed that high BMI was independently associated with the decreased risk of all‐cause death. Conclusions: Obese patients appear to have a lower long‐term mortality than do non‐obese patients in CTO after successful PCI using DES. © 2017 Wiley Periodicals, Inc.